2023
DOI: 10.3390/bioengineering10070760
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Nanomaterials-Based Targeted Drug Delivery for Preclinical Cancer Diagnosis and Therapeutics

Abstract: Nano-oncology is a branch of biomedical research and engineering that focuses on using nanotechnology in cancer diagnosis and treatment. Nanomaterials are extensively employed in the field of oncology because of their minute size and ultra-specificity. A wide range of nanocarriers, such as dendrimers, micelles, PEGylated liposomes, and polymeric nanoparticles are used to facilitate the efficient transport of anti-cancer drugs at the target tumor site. Real-time labeling and monitoring of cancer cells using qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 183 publications
0
15
0
Order By: Relevance
“…It has also been demonstrated that platinum and palladium nanozymes have more efficient catalase-mimicking activity than gold and silver nanoparticles, which explains why platinum is widely used in biosensing and PDT (photodynamic therapy). 63,64 On the other hand, studies have also unveiled that FeNPs act as catalase mimetics at high pH and as peroxidase mimetics at lower pH. 65 This evidence was supported by the fact that FeNPs entrapped in lysosomal vesicles at low pH cause cell death by exhibiting peroxidaselike activity, while they cause no damage to the cells in the cytoplasmic environment, where they exhibit catalase-like activity at neutral pH.…”
Section: ■ Nanozymes: Structure and Functionsmentioning
confidence: 99%
“…It has also been demonstrated that platinum and palladium nanozymes have more efficient catalase-mimicking activity than gold and silver nanoparticles, which explains why platinum is widely used in biosensing and PDT (photodynamic therapy). 63,64 On the other hand, studies have also unveiled that FeNPs act as catalase mimetics at high pH and as peroxidase mimetics at lower pH. 65 This evidence was supported by the fact that FeNPs entrapped in lysosomal vesicles at low pH cause cell death by exhibiting peroxidaselike activity, while they cause no damage to the cells in the cytoplasmic environment, where they exhibit catalase-like activity at neutral pH.…”
Section: ■ Nanozymes: Structure and Functionsmentioning
confidence: 99%
“…Active targeting involves ligands or antibodies that can recognize biomarkers associated with multidrug-resistant (MDR) cancer cells, enabling the targeted targeting of these drugresistant cells (Tiwari et al, 2023;Yu et al, 2010). This can be achieved by functionalizing drug delivery systems, such as nanocarriers, with these ligands or antibodies (Seidu et al, 2022).…”
Section: Controlled Drug Releasementioning
confidence: 99%
“…By optimizing drug delivery efficiency and enhancing tumor targeting, bioactive-based nanocarriers have the potential to improve treatment efficacy, leading to better disease control and prolonged patient survival. 53 Furthermore, bioactive-based nanocarriers offer the potential to reduce systemic toxicity associated with conventional chemotherapy by minimizing drug exposure to healthy tissues. Through targeted delivery to cancer cells and the tumor microenvironment, nanocarriers can enhance therapeutic efficacy while minimizing off-target effects, thereby improving the overall safety profile of cancer treatments.…”
Section: Preclinical and Clinical Studiesmentioning
confidence: 99%